Early Detection of Children's Emotional and Behavioral Problems during the Covid-19 Pandemic - Muhaini Atmayana Purba; Wardiyah Daulay (Talenta Publisher, 2022)
Children's emotional and behavioral problems differ from one another with theÂ same background. Both decrease children's interaction, learning process, and behavior. The indicators of emotional problems verily affect children's behavior which causes them to be vulnerable in facing daily life obstacles. In terms of the learning process, they will have difficulty interacting and controlling their emotions and behavior. This study aims to identify emotional and behavioral problems of school-age children from SDN 060866 Medan Timur during the Covid-19 pandemic. This study used quantitative research with descriptive methods. Non-probability sampling using a total sampling technique was conducted with a total sample of 97 people. The sampling results showed that 52.6% of students sit in class VI, 51.5% are aged 12 years old, 61.9% are male, 56.7% are Javanese, 88.7% students with high-school graduated fathers, and 77.3% of students with high-school graduated mothers. The study's results indicate that 71.1% of students with emotional problems are in the borderline category and 71.1% in the normal category of behavioral problems. Therefore, it is imperative to detect children's emotional and behavioral problems early. It will prevent further problems so the children can grow and develop properly. Â